Epidemiological and clinical profile of patients undergoing cholecystectomy: a narrative review - Leite, Rafael Rodrigues; Gomes, Sara Maria Bié; de Sousa, Joyce Lima; Ferreira, Ingryd de Sá Barreto; Ferreira, Sávio Benvindo (Disciplinarum Scientia | Saúde, 2024)
Objective: Therefore, the present study aims to identify the epidemiological and clinical profile of patients undergoing cholecystectomy with the aim to facilitate early diagnosis and treatments. Methodology: This is a narrative review of a qualitative and descriptive nature, using articles from 2018 to 2023 that provided information about the epidemiological and clinical profile of patients undergoing cholecystectomy, searched in the following databases: VHL, Embase, Pubmed. Results: Were found 303 articles, 25 of which were in the VHL; 98 Embase, 180 in Pubmed, after applying the exclusion criteria, remaining 20 articles. Conclusion: The epidemiological profile of patients undergoing cholecystectomy consists of women with an average age of 53 years, who are overweight and smokers. Regarding the clinical profile, the main manifestation is abdominal pain in the right upper quadrant, followed by nausea and vomiting; with cholelithiasis being the main indication for performing cholecystectomy, followed by cholecystitis, also the main complication encountered.